2008
DOI: 10.1371/journal.pone.0001640
|View full text |Cite
|
Sign up to set email alerts
|

Brain Neuronal CB2 Cannabinoid Receptors in Drug Abuse and Depression: From Mice to Human Subjects

Abstract: BackgroundAddiction and major depression are mental health problems associated with stressful events in life with high relapse and reoccurrence even after treatment. Many laboratories were not able to detect the presence of cannabinoid CB2 receptors (CB2-Rs) in healthy brains, but there has been demonstration of CB2-R expression in rat microglial cells and other brain associated cells during inflammation. Therefore, neuronal expression of CB2-Rs had been ambiguous and controversial and its role in depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
202
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(213 citation statements)
references
References 33 publications
5
202
3
3
Order By: Relevance
“…In this context, it is also interesting to note that a number of recent studies have demonstrated a role for the CB 2 receptor, classically associated with the immune system, in anxiety-and depression-related behaviour. Thus, intracerebroventricular administration of antisense oligonucleotide sequence directed against CB 2 mRNA reduced anxiety-like behaviour in the mouse elevated plus-maze (Onaivi et al, 2008). Moreover, a high incidence of the Q63R polymorphism in the CB 2 receptor gene was found in Japanese subjects diagnosed with depression (Onaivi et al, 2008).…”
Section: Stress-induced Analgesiamentioning
confidence: 97%
See 1 more Smart Citation
“…In this context, it is also interesting to note that a number of recent studies have demonstrated a role for the CB 2 receptor, classically associated with the immune system, in anxiety-and depression-related behaviour. Thus, intracerebroventricular administration of antisense oligonucleotide sequence directed against CB 2 mRNA reduced anxiety-like behaviour in the mouse elevated plus-maze (Onaivi et al, 2008). Moreover, a high incidence of the Q63R polymorphism in the CB 2 receptor gene was found in Japanese subjects diagnosed with depression (Onaivi et al, 2008).…”
Section: Stress-induced Analgesiamentioning
confidence: 97%
“…The CB 2 receptor is expressed in tissues and cells of the immune system (Munro et al, 1993;Parolaro, 1999). Its localization on glial cells (Cabral and Marciano-Cabral, 2005;Massi et al, 2008;Walter et al, 2003) means that it too may be capable of modulating central nervous system functioning and some recent evidence also suggests that CB 2 receptors may be expressed in neurones (Gong et al, 2006;Onaivi et al, 2008;Van Sickle et al, 2005). The above is a cursory introduction to a signalling system whose intriguing complexity has become more and more evident with the proliferation of research papers on this topic in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The first results showed increased CB2r gene expression in the brain of mice after chronic treatment with heroin or cocaine and decreased CB2r gene expression in striatum and ventral midbrain of mice after chronic ethanol intake (Onaivi et al, 2008a). In fact, mice that developed alcohol preference presented reduced CB2r gene expression, and chronic treatment with JWH015, a CB2r agonist, enhanced alcohol consumption in stressed mice, whereas the administration of the CB2r antagonist AM630 reduced alcohol intake in stressed mice (Ishiguro et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the Q63R polymorphism of the CB2 gene is associated with alcoholism and depression in Japanese individuals (29,30). Moreover, this polymorphism may predispose to the development of childhood immune thrombocytopenic purpura in independent populations from Italy (31) and Egypt (32).…”
Section: Discussionmentioning
confidence: 98%